Rancang Bangun Modul Trainer Praktikum Pneumatic Berbasis PLC Outseal Untuk Mahasiswa Teknik Elektro Politeknik Negeri Pontianak: Indonesia - Hasan; Riyanto, Agus; Chrysostomos Hendro Yuwono, Yohannes (Jurnal ELIT, 2025)
The development of technology in various industrial fields is currently experiencing rapid progress. The use of machines, especially hydraulic pneumatics, is used in processing or producing goods. In order for students to understand the technology, a trainer module is needed which is used as a learning tool related to how hydraulics and pneumatics work. This study was conducted with the aim of creating a trainer module used in the Pneumatic and Hydraulic Systems course. PLC ousteal is used to control pneumatics to match the settings in the industry. This study uses a data collection method that includes testing the module with questions and competency strengthening test questions. Through a questionnaire In analyzing the results of the study using quantitative descriptive analysis. The results of the data obtained in the form of the use of a trainer module help students understand pneumatics and hydraulics. From the results of the experiment on 30 students, 25 were successful according to the scenario that had been made. With 18 people being able to complete it in less than 60 minutes.